2020
DOI: 10.1097/md.0000000000022228
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study to evaluate the maximum tolerated dose of the combination of SH003 and docetaxel in patients with solid cancer

Abstract: Introduction: Cancer is the second leading cause of death, and the burden of cancer continues to grow globally. Research on the efficacy of combined administration of herbal medicine and anticancer drugs is also increasing. SH003 is a new herbal medicine composed of Astragalus membranaceus , Angelica gigas , and Trichosanthes kirilowii . SH003 alone up to 4800 mg daily was found to be safe. Preclinical studies have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Although herbal medicines are useful for symptom management, additionally utilizing the anticancer properties of herbal medicines tends to maximize their potential. The anticancer actions of herbal medicines are increasingly being investigated, and several studies are being performed to confirm the effects of co-administration of herbal medicines and anticancer drugs [18,19] . There is greater clarity regarding the mechanisms underlying the synergistic interactions between these agents, although further research is warranted to gain a deeper understanding of the subject [20–22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although herbal medicines are useful for symptom management, additionally utilizing the anticancer properties of herbal medicines tends to maximize their potential. The anticancer actions of herbal medicines are increasingly being investigated, and several studies are being performed to confirm the effects of co-administration of herbal medicines and anticancer drugs [18,19] . There is greater clarity regarding the mechanisms underlying the synergistic interactions between these agents, although further research is warranted to gain a deeper understanding of the subject [20–22] .…”
Section: Discussionmentioning
confidence: 99%
“…No-observed-adverse-effect level (NOAEL) of SH003 determined by phase I clinical trials was 4,800 mg/day [ 41 ]. Maximum tolerable dose (MTD) of docetaxel in cancer patients was 75 mg/m 2 [ 40 ]. Animal equivalent dose was calculated by the following equation [ 47 ]: …”
Section: Methodsmentioning
confidence: 99%
“…e anticancer effect of SH003 against breast, lung, and prostate cancer has been demonstrated through several in vitro and in vivo studies [30][31][32][33][34][35][36][37][38]. e safety of SH003 was proved by phase I clinical study for solid tumors, and phase II clinical study for wildtype EGFR lung cancer patients is in progress [39][40][41]. Meanwhile, phase I/II clinical study of SH003 combined with docetaxel for breast and lung cancer patients is also in progress (NCT01755923, https://clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…A phase I study evaluating the maximum tolerated dose for SH003 administration alone confirmed the daily safe dose to be up to 4800 mg [ 17 ]. A clinical trial to ensure the maximum tolerated dose when administered in combination with docetaxel is also being conducted [ 18 ].…”
Section: Characteristics Of Sh003mentioning
confidence: 99%